MINDSET AWAL SISWA TERHADAP PEMBELAJARAN MATEMATIKA YANG SULIT DAN MENAKUTKAN - Devi Nur Fitriana; Alifatul Aprilia (Pedir Research Institut, 2021)
Learning mathematics is one of the lessons with abstract concepts that require students to solve problems contained in math problems, which cannot be separated from everyday life. Mathematics lessons are considered difficult because it comes from students' initial perceptions of mathematics who already think that mathematics is difficult. The opinion that mathematics is a difficult subject has been passed down by students from generation to generation and has become a bad mindset. For this reason, all parties involved in learning mathematics must be able to combat the bad mindset by being given positive encouragement to become a positive minds